Syaikh Ahmad Sirhindi's unity of vision (Wahdat al-Syuhud) versus Ibn 'Arabi's to the reality unity of being (Wahdat al-Wujud) with reference of existence / Ahmad Daud Ishak El-Merbawiy - Ishak El-Merbawiy, Ahmad Daud (Unit of Research, Development and Commercialization (URDC),UiTM Perlis & University Publication Centre (UPENA), 2004)
This writing will focus on the Concept of Existence and Reality. Ahmad Sirhindi's standpoint on the Interpretation of wahdat al-wujud and wahdat al-shuhud would be taken as the basis for discussion. Through this investigation, an analysis into the meanings of Ontology and Epistemology would be made within the two concepts. From the analysis, I hope this writing would be revealed as the reconstruction of truth and certainty from Muslim Sufi's standpoint. Subsequently, the inference of true knowledge would appear as the scientific truth resulting from the highest order of the Divine System of Knowledge.